Pengaruh Penyerapan Anggaran, Budaya Organisasi, Kepuasan Kerja Dan Pengawasan Inspektorat Terhadap Kinerja Keuangan Organisasi Publik (Studi pada Pemerintah Daerah Kabupaten Banjarnegara) - Dimas Estu Priagung; Edward K. Sinoeraya; Mafudi Mafudi (Al-Tijary, 2016)
This study aims to determine the absorption of the budget, organizational culture, job satisfaction and supervision inspectorate on the financial performance of public organizations. The research object is selected in this study were employees of the SKPD in Banjarnegara district. The research is a qualitative research with empirical studies. Criteria respondents used in this study are employees who work on the part relating to the study variables. The sample used by 54 respondents. Data collection methods used with a questionnaire consisting of five instruments by using Likert scale. Of the 54 questionnaires that have been distributed, the number of questionnaires returned by 54 questionnaires and can be analyzed. Data analysis technique used is test the quality of data consisting of validity and reliability test, test the classical assumption of normality test, multicollinearity and test heterosketastistas, and hypothesis testing consisting dariuji multiple regression coefficient ddeterminasi, t test and F.These results indicate that ( 1 ) absorption positive significant effect on the financial performance of public organizations ( 2 ) organizational culture positive significant effect on the financial performance of public organizations ( 3 ) job satisfaction did not significantly affect the financial performance of public organizations ( 4 ) supervision inspectorate effect a significant positive financial performance of public organizations.